E-Auction Sebagai Instrumen Tata Kelola Kolaboratif: Upaya Peningkatan Akuntabilitas Lelang Barang Miliki Negara - Wibowo, Leily Kunti; Wiyaka, Agus; Murti, Endang (Kolaborasi : Jurnal Administrasi Publik, 2026)
The management of state assets requires transparency, efficiency, and accountability, particularly in the implementation of auctions for Barang Milik Negara (BMN). The increasing adoption of digital technology has encouraged the use of electronic auction (e-auction) systems to improve public service delivery. This study aims to analyze the implementation of the e-auction system and its contribution to enhancing accountability in BMN auctions at KPKNL Madiun. The research employs a qualitative approach with a descriptive design, utilizing data collected through in-depth interviews, observation, and documentation. Informants were selected purposively, including auction officials, technical staff, and auction participants. The findings reveal that the e-auction system is implemented through integrated digital stages, including participant registration, auction announcement, bidding process, winner determination, and payment settlement. The system significantly enhances transparency through real-time information access and digital recording of all auction activities, ensuring traceability and auditability. Additionally, the implementation of e-auction improves administrative efficiency and increases public participation, which contributes to more competitive bidding and optimal auction outcomes. However, challenges remain, particularly in terms of limited digital literacy and the need for broader socialization of the system. In conclusion, the e-auction system plays a crucial role in strengthening accountability in BMN auction processes by promoting transparency, efficiency, and wider public access. Despite its positive impact, the effectiveness of the system is influenced by external factors such as user readiness and technological understanding.